The association of depression, anxiety and stress with dietary intake among adults in Klang Valley Selangor / Nur Nazurah Yunos - Yunos, Nur Nazurah (2016)
Depression, anxiety and stress are the most studied and reported form of mental illnesses. The burden of these psychological disorders seems to be increasing among adults in Malaysia. These psychological disorders are most well-known factors that have been associated with problems in dietary intake of an adult. The main objective of this study was to determine the level of depression, anxiety, and stress of adults around Klang Valley. Besides, this research was conducted to determine the association between depression, anxiety, and stress with dietary intake. A cross sectional study design will be used to determine the prevalence of depression, stress and anxiety and its associated factors among 71 participants who lives at area around Klang Valley, Selangor. One-way A nova is used to determine whether there are any significant differences between the means of variables. Characteristics of subjects were described as means, standard deviations, and median. Normality was assessed using boxplots and histograms and Kolmogorov-Smimov test. Pearson correlation test used to determine the relationship between depression, anxiety, and stress with dietary intake. Mean with standard deviation was used to present the comparison of the mean data. The overall prevalence of depression, anxiety and stress among adults were 22.5%, 47.9% and 22.5% respectively. Male had a higher prevalence of depression, anxiety and stress than female. For the conclusion, this study suggests that there are certain risk factors other than dietary intake which predispose adults to psychological disorder such as stress, anxiety and depression. Prevalence of depression and stress among adults in Klang Valley was low, however prevalence of anxiety was high. There was no association between anxiety and stress with energy intake. However, there is an association between depression and high energy intake.